A participatory research to assess how a student citizens’ assembly can facilitate the co-creation of nutrition interventions in higher education settings - Alice Bellicha; Benjamin Allès; Julia Baudry; Lucile Bouré; Henri Dehove; Hajar El Karmouni; Emilie Frenkiel; Emmanuelle Kesse-Guyot; Sandrine Péneau; Malo Mofakhami; the USPN Student Citizens’ Assembly Group (BMC Public Health)
Abstract Background The transition period from adolescence to early adulthood is critical for developing new nutritional behaviors, making higher education students an important target group for public health nutrition interventions. Given the complexity of nutrition-related behaviors and their various determinants, involving the student population (the future beneficiaries of interventions) and the partners engaged in their implementation when designing campus nutrition interventions is essential. Citizens’ assemblies are deliberative processes which are more and more frequently organized to co-create solutions to complex problems. This study aims 1) to design and implement a student citizens’ assembly using participatory research methods, 2) to describe its process and evaluate its transferability, 3) to evaluate changes in dietary habits, knowledge and citizen practices among students participating in this assembly. Methods This study will take place at a French university (University Sorbonne Paris Nord, USPN) located in socio-economically disadvantaged suburbs of Paris. The student citizens’ assembly will gather a mini-public of 30 students enrolled at the time of the study and a co-creation team of academic and non-academic partners involved in student life, nutrition, physical activity, or public policies. The aim of the assembly is to co-create a set of concrete proposals that would enhance USPN students’ access to sustainable diets and physical activity. The protocol is based on a continuous process evaluation and a pre-post design among the mini-public. A mixed-method framework combining quantitative and qualitative approaches will be developed. This study will make use of (i) field observations of the intervention process and transferability, (ii) data collected by questionnaires on pre- and post- dietary habits, knowledge and citizen practices of the mini-public, and (iii) pre-post interviews with a subsample of the same mini-public. Discussion Relying on participatory research methods, this study will provide new insights into involving higher education students and diverse partners in co-creating campus nutrition interventions. Through the collaborative work of researchers, higher education students, university representatives, public institutions, and local and community actors, this study will provide evidence-based guidance for designing innovative and contextually-relevant nutrition interventions in the higher education setting. Trial registration This research was registered at the ClinicalTrial.gov (NCT06580795; registration date: 2024–08-30; https://www.clinicaltrials.gov/study/NCT06580795 ).